Pancreatitis Developing in the Context of Acute Hepatitis: A Literature Review - Khedmat, Hossein; Ghamar-Chehreh, Mohammad Ebrahim; Agah, Shahram; Aghaei, Aghdas (JOP. Journal of the Pancreas, 2015)
Despite strong evidence suggestive of associations between hepatic diseases and pancreas injury, a potential relationship between acute hepatitis and acute pancreatitis has not been a matter of review; which we focused on in the current paper. Some of the main findings of this review article are: fulminant hepatitis failure represents the highest incident rate of hepatitis-related acute pancreatitis; so a screening program might be indicative in these patients. Specific characteristics of HAV-related pancreatitis are that it is a benign condition with no reported mortality; and a male preponderance in the incidence, with females developing in older ages and having shown the signs of both conditions simultaneously. The incidence of acute pancreatitis in HBV infection is the lowest, but the mortality was the highest. HEV-related acute pancreatitis was most likely to represent pseudocysts and there was an apparent ethnic-priority with Indian descents, the only reported cases in the literature. Hepatitis-related pancreatitis in liver transplant recipients was most frequent in HBV infected patients; and in IFN-induced pancreatitis, cessation of the drug was most effective in treatment, with no catastrophic event reported. Image: Baqiyatallah University of Medical Sciences logo. Tehran, Iran.